Granulation Red Index To Assess Pressure Ulcer Granulation Tissue Quality Treated By Honey Gauze Dressing By Digital Image Analysis - Fortuna, Fory; Putri, Nandita Melati; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2019)
Background : Good formation of granulation tissue in the ulcer bed is regarded as one of the indicators of pressure ulcer healing. Granulation red index (GRI) had been published as an objective parameter to assess the quality of granulation tissue. Honey stimulates granulation of tissue and creates a moist healing environment. However, the assessment of granulation tissue quality of pressure ulcers treated by honey has yet to be proven in clinical settings. In this study, we evaluate the granulation tissue quality of pressure ulcers treated by honey using granulation red index by digital image analyses. Method: There were 12 subjects who fulfill inclusion criteria treated by honey gauze dressing and were evaluated every week for three times measurements of %GRI and DESIGN-?score. Parameters of this study were the delta %GRI80 and DESIGN-?R score. Correlations were evaluated by Spearman’s correlation coefficient. Result : The correlation of delta GRI80% and DESIGN-?R score was statistically significant from baseline measurement to first week of treatment and to second week of treatment (r1=0.65, p1=0.02 and r3=0.832, p2=0.001). The correlation of delta GRI80% and DESIGN-?R score from first to second week therapy was not statistically significant (r=0.23, p=0.47), but the GRI80% from first week therapy to second week of therapy was increasing and DESIGN R score was decreasing. Conclusion:This study shows the correlation of %GRI80 and DESIGN-?R score of pressure ulcer after the treatment of honey gauze dressing. This study hopefully assists further study for wound bed preparation assessment and treatment of pressure ulcer for surgical intervention.